Large Memory Window of van der Waals Heterostructure Devices Based on MOCVD‐Grown 2D Layered Ge4Se9. Issue 41 (9th September 2022) - Noh, Gichang; Song, Hwayoung; Choi, Heenang; Kim, Mingyu; Jeong, Jae Hwan; Lee, Yongjoon; Choi, Min‐Yeong; Oh, Saeyoung; Jo, Min‐kyung; Woo, Dong Yeon; Jo, Yooyeon; Park, Eunpyo; et al.
Abstract: Van der Waals (vdW) heterostructures have drawn much interest over the last decade owing to their absence of dangling bonds and their intriguing low‐dimensional properties. The emergence of 2D materials has enabled the achievement of significant progress in both the discovery of physical phenomena and the realization of superior devices. In this work, the group IV metal chalcogenide 2D‐layered Ge4 Se9 is introduced as a new selection of insulating vdW material. 2D‐layered Ge4 Se9 is synthesized with a rectangular shape using the metalcorganic chemical vapor deposition system using a liquid germanium precursor at 240 °C. By stacking the Ge4 Se9 and MoS2, vdW heterostructure devices are fabricated with a giant memory window of 129 V by sweeping back gate range of ±80 V. The gate‐independent decay time reveals that the large hysteresis is induced by the interfacial charge transfer, which originates from the low band offset. Moreover, repeatable conductance changes are observed over the 2250 pulses with low non‐linearity values of 0.26 and 0.95 for potentiation and depression curves, respectively. The energy consumption of the MoS2 /Ge4 Se9 device is about 15 fJ for operating energy and the learning accuracy of image classification reaches 88.3%, which further proves the great potential of artificial synapses. Abstract : Ge4 Se9, a new insulating 2D‐layered material, is synthesized using metal–organic chemical vapor deposition at 240 °C with low‐reactive precursors. The 2D‐layered Ge4 Se9 forms a low band offset with MoS2, exhibiting a large memory window with linear gate‐tunability. As an artificial synapse, the MoS2 /Ge4 Se9 heterostructure exhibits synaptic updates with low non‐linearity of 0.26 and low energy consumption of 15 fJ.